Fórmulas infantis para lactentes de 0-6 meses com adição dos ácidos graxos docosahexaenóico e araquidônico: análise de rotulagem e lipídeos - Luciana Marques Carabetti Gontijo (2016)
Human milk is the only food capable of providing, in quantity and quality, all the nutrients, energy, and immunomodulatory substances for newborns. However, when there are situations that make breastfeeding impossible (mothers with HIV or children born with severe problems in metabolism), or no access to milk banks, the most suitable alternative food source are infant formulas. There are, in the Brazilian market, many infant formulas with varying compositions, making necessary the constant evaluation of its quantity and quality nutritional adequacy, inasmuch as the young children feeding affects the development of the individual throughout his life. The aim of this study was: (a) determine - in infant formulas for infants from 0 to 6 months added fatty docosahexaenoic acid (DHA) and arachidonic fatty acid (ARA) - the total lipid content, fatty acid profile, quantification of DHA, ARA, linoleic and - linolenic; (B) assess the nutritional adequacy of the label according to the laws in force in Brazil; (C) evaluate the daily intake proposed by the manufacturer in relation to international recommendations. To this purpose, we used initially the Roese Gottlieb method for the quantification of total lipids and, for the other analyzes, we used gas chromatography with mass spectrometry. For labeling assessment data we employed the Resolution 43/2011 and the international recommendations of the World Health Organization, Dietary Reference Intakes, and European Food Safety Authority. We found significant differences for less in total lipid content between 3 of the 4 analyzed formulas, however a 20% tolerance provided for by law make them legally appropriate. Regarding fatty acids DHA, ARA, linoleic and - linolenic acid, we found a significant difference compared to the stated on the labels of the formulas under study. The DHA and ARA were less concentrated than reported by the manufacturer, 18% to 37% and 46% to 56%, respectively, and, in the opposite way, linoleic fatty acids and - linolenic acid in a higher concentration than indicated in the label. In both cases in only one of the formulas the fatty acids were in agreement with the provisions of Brazilian law, even with the tolerance of 20% in nutritional value. Nutrition labeling was legally appropriate to resolution number 43 of 2011 for all nutrients. The proposed daily intake made by manufacturers for infants proved to be inadequate. We found excess of proteins, carbohydrates and energy, and deficiency of DHA and ARA. It was noted, finally, that although the labels are adequate, the formulas were inadequate in quantity and quality of nutrients, to the Brazilian laws. In relation to international recommendations, both labels and formulas were inadequate in quantity and quality of nutrients.